Assessment of the genetic structure of European bison (Bison bonasus L.) from Bialowieza by single nucleotide substitutions of DRB3 and DQB genes of major histocompatibility complex (European Bison Conservation Newsletter, 2015)
Differences in SNP-substitutions of the major histocompatibility complex (MHC) DRB3 and DQB genes involved in the immune response were shown in the genetic structure of the Belarusian and Polish populations of European bison. Unique and rare alleles, which are valuable for the population, and will contribute to an increase in genetic diversity and the viability of the species, were identified.
Keywords: European bison; Bison bonasus; frequency of DRB3 and DQB genes; major histocompatibility complex